Assess Main Breaks for Distribution System Optimization. Issue 3 (1st March 2014) - Martin, Barb; Ries, Tom
Abstract : Main breaks are a reality of every distribution system, but comprehensive data collection and analysis can help identify influencing factors and lead to improved control and planning.